A Cross-Layer Cooperation Mechanism of Wireless Networks Based on Game Theory. (10th March 2014) - Chunsheng, Cui; Yongjian, Yang; Liping, Huang
To meet the wireless network congestion control problem, we give a definition of congestion degree classification and propose a mechanism of directed cooperative path net, guided by the wireless network's cross-layer design methods and node cooperation principles. Considering the virtual collision and "starved" phenomenon in congested networks, the QRD mechanism and channel competition mechanism QPCG are proposed, with introducing the game theory into the cross-layer design. Simulation results showed that directed cooperative path nets could effectively improve network resource utilization and network transmission performance in congested network. And the QRD and QPCG mechanism could effectively reduce the probability of "starved" phenomenon and increased the wireless network throughput with reducing the packet loss rate.